Application of pid-fuzzy control for pendubot - Tran Hoang Chinh; Nguyen Minh Tam; Nguyen Van Dong Hai (Journal of Technical Education Science, 2017)
PID is a classical control method. Control parameters of PID can be chosen due to experts’ experiences, error test or searching algorithm, such as, genetic algorithm (GA) or swarm algorithm (SA). However, the fact that parameters , , are fixed in operating time of system describes a disadvantage which makes system non-flexible enough to adapt highly with system’s condition. This paper presents a method of using fuzzy algorithm to change flexibly control parameters of PID when system operates. Thence, control quality is improved. Object which is used for testing in this paper is pendubot- a popular model in laboratories of control engineering, balance control for pendubot at Top position as a requirement. Using PID-Fuzzy algorithm for this model is proved to be more optimal than PID through simulation (Matlab/Simulink) and experiment.